IMPLIKATUR PELANGGARAN PRINSIP KERJA SAMA DALAM VIDEO INSTAGRAM PADA AKUN @UNCLE CIMBO - Faizah, Hasnah; Charlina, Charlina; Nur'azizah, Dewi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The implicature is that the meaning conveyed is different from the utterance uttered. The implicature is usually used by someone to convey something not directly in order to cause a certain effect, or the utterance must be communicated and there is no other way to convey it in certain situations. The purpose of this study is to describe implicatures due to violation of the principle of cooperation contained in instagram video on Uncle Cimbo account. Data were collected from 144 video landing @Uncle Cimbo. The video is transcribed gradually. Technique of collecting data using method refer to technique note. The stages of data collection is the author watched the video in the uncle Cimbo account. The researcher listened to the content of the instagram video conversation by paying attention to every context of the conversation. Based on the research, implicatures due to the offenders The principle of cooperation found in Video instagram @Uncle Cimbo found 22 conventional implicatures, implicatures due to maximal breaches of quantity found as many as 39 data, implicatures due to quality 21 maximal breaches, and implicatures due to maximal relevance breaches 34 data, and implicatures due to maximal way violations of 44 data. So in this study the implicatures resulting from frequent violations are implicatures resulting from maximal violations of 44 data.Keywords: implicatur, breach of cooperative principle, instagram video, @Uncle Cimbo